The Effect of Group Identity on Support for Political Violence: Evidence from Northern Ireland - Canavan, Miceal (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2023)
Why do people support political violence in peaceful contemporary democracies? In recent years scholars have increasingly sought to understand what drives individuals to adopt radical attitudes in societies where there is not active conflict and where peaceful democratic competition is the norm. This nascent strand of literature has identified a number of important determinants such as individual predispositions, personality traits, catalytic political events and other important contextual factors. Furthermore, reflecting classic work on civil conflict this new research has also emphasised the centrality of group identity. This thesis seeks to build on this work on the relationship between group identity and support for political violence. More specifically, it analyzes how multiple overlapping group identities shape open support for political violence in different ways, how they influence the concealment of attitudes towards political violence, and finally how they moderate the way in which high profile acts of political violence influence attitudes towards political violence. Alongside this it also contributes to the literature on the political determinants of support for political violence, and the surprising way in which gender influences these radical attitudes. To test the arguments presented it focuses on Northern Ireland and employs multivariate regression analysis of survey data, list experiments, and unexpected event during survey design analysis.
APPROVED
Keywords: identity; political violence